STRUCTURE OF STUDENT'S VOCATIONAL INTEREST BASED ON FACULTY AT THE SEMARANG STATE UNIVERSITY - Binti Iis (Universitas Pendidikan Indonesia, 2023)
Vocational interests have an important position in a person because they can predict educational choices, performance at work, career success, and personal history in the future. At Semarang State University, most students who change majors show that the chosen major is not available to their interests. This study aims to map the structure of students' vocational interests. The study uses a quantitative approach with a survey method. The population in this study was second-semester students with a total sample of two hundred and thirty-two taken from five faculties. This research using the Vocational Interest Inventory instrument developed by Tracey, which has been adapted, consists of eight indicators, namely social facilitating, managing, business detail, data processing, mechanical, nature, artistic, and helping with forty-eight items. This research use data analysis with descriptive statistics and different tests with the Kruskal Wallis test. The results of this study can be used as the basis for developing a career counseling program by considering students' vocational interests to lead students to the expected career choices.